A first course in systems biology - Voit, Eberhard O.; CRC Press (Boca Raton, FL : CRC Press, an imprint of Garland Science, 2017)
A First Course in Systems Biology is an introduction for advanced undergraduate and graduate students to the growing field of systems biology. Its main focus is the development of computational models and their applications to diverse biological systems. The book begins with the fundamentals of modeling, then reviews features of the molecular inventories that bring biological systems to life and discusses case studies that represent some of the frontiers in systems biology and synthetic biology. In this way, it provides the reader with a comprehensive background and access to methods for executing standard systems biology tasks, understanding the modern literature, and launching into specialized courses or projects that address biological questions using theoretical and computational means.
chapter 1 Biological Systems -- chapter 2 Introduction to Mathematical Modeling -- chapter 3 Static Network Models -- chapter 4 The Mathematics of Biological Systems -- chapter 5 Parameter Estimation -- chapter 6 Gene Systems -- chapter 7 Protein Systems -- chapter 8 Metabolic Systems -- chapter 9 Signaling Systems -- chapter 10 Population Systems -- chapter 11 Integrative Analysis of Genome, Protein, and Metabolite Data: A Case Study in Yeast -- chapter 12 Physiological Modeling: The Heart as an Example -- chapter 13 Systems Biology in Medicine and Drug Development -- chapter 14 Design of Biological Systems -- chapter 15 Emerging Topics in Systems Biology.
Keywords: Computational biology; Systems biology